RANCANG BANGUN SISTEM GREENHOUSE PADA MEDIA TANAM AEROPONIK DENGAN MENGGUNAKAN ARDUINO DAN SINGLE BOARD COMPUTER - Arfian Nurfi Pangestu; n/a Nurussaâ€™adah; Ponco Siwindarto (Jurnal Mahasiswa TEUB, 2023)
Aeroponics is a method of growing plants in a hanging root position and providing water and nutrients by misting the roots of the plants. In this research the authors designed a system that can condition the environment in a greenhouse using aeroponic growing media with parameters of air temperature, air humidity, and light intensity. In this design, the DS18B20 sensor is used as a temperature detector, the DHT11 sensor as a humidity detector, and the LDR sensor as a light intensity detector. The results of the DHT11 sensor test compared to the HTC-2 thermometer obtained an average error of 2.77%, the DS18B20 sensor test compared to the HTC-2 thermometer obtained an average error of 3.34%, the LDR sensor test compared to the AS803 luxmeter obtained errors that vary each test. The measurements results from the sensor will be processed by Arduino Uno and Single Board Computer to control the actuator connected to the relay. In this system to condition the environment, there are air temperature parameters controlled using a DC fan, air humidity controlled using a mistmaker and lighting controlled using an LED grow light. This environmental conditioning system is capable of lowering the temperature by 0.5Â°C with an average length of time of 2:18 minutes, increasing the air humidity by 5% RH with an average length of time of 4:20 minutes, and turning on the LED growlight when the light intensity is low. of 50lux according to the program. The automatic watering system in the form of mist uses an Arduino Uno timer with a water pump and a 0.3mm nozzle. From the results of sensor testing and the results of testing the environmental conditioning system, it shows that the designed system can work well according to the expected design. Keywords: Aeroponics, greenhouse, lighting, temperature, humidity, watering